Genomic analysis of Enterococcus faecium from non-clinical settings: antimicrobial resistance, virulence, and clonal population in livestock and the urban environment - Lopes, Jéssica; de Lencastre, Hermínia; Conceição, Teresa (Frontiers in Microbiology, 2024)
Enterococci are commensals of the gastrointestinal tract of humans and animals that evolved into opportunistic pathogens with high antimicrobial resistance and virulence. Multidrug resistant Enterococcus are a major cause of hospital-acquired infections worldwide. For this reason, the characterization of non-clinical reservoirs of Enterococci, their epidemiological link to resistant hospital isolates is crucial for controlling their spread. A total of 295 samples collected from livestock (pigs and cows, n=135) and environment (public buses, passengers hands and urban environments, n=160) were screened for Enterococcus spp. Enterococci were detected in 90.5% (n=267) of the samples, with a higher prevalence in livestock (100%) compared to the environment (82.5%, p<0.0001), but none of the isolates exhibited vancomycin resistance. E. faecalis was the most prevalent species (51.7%), predominantly found in livestock (62.2%), while E. faecium was more common in the environment. E. faecium antimicrobial resistance profiles, virulence potential and clonal population were further characterized. Of the 59 E. faecium isolates, 78% showed resistance to ≥3 antibiotic classes and contained associated resistance genes, namely tetracyclines (tetM and tetL), beta-lactams (mutations in pbp5) and high-level resistance to aminoglycosides (ant(6)-Ia and aac(6')-aph(2'')). A wide array of virulence factors was detected among E. faecium, associated to adherence, biofilm formation and adaptation to host response, while hospital associated virulence markers, as IS16, were less frequent, probably due to the non-clinical nature of the isolates. Clonal population analysis revealed a diverse E. faecium population. Although no direct epidemiological link could be traced between our isolates and specific clinical isolates, infection associated genetic backgrounds were identified in non-clinical isolates: one isolate from pigs belonged to CC17 (ST32), while four isolates belonged to CC94, including one recovered from pigs (ST296), one from cows (ST2206), one from the urban environment (ST1205) and other from buses (ST800).In summary, this study underscores a high prevalence of clinically relevant Enterococcus species among healthy livestock and the environment. Despite the absence of vancomycin resistance and limited hospital-infection associated clonal lineages, the presence of E. faecium with significant virulence potential and resistance to critical antibiotics in human and veterinary medicine, highlights the need for continuing surveillance of non-clinical reservoirs.